How School Dictionaries Treat Human Reproductive Organs, and Recommendations for South African Primary School Dictionaries - Hiles Morris, Lorna (Lexikos, 2022)
This paper is a pilot study that investigates options for treating human reproductive organs in primary school dictionaries in South Africa, with particular emphasis on illustrations. The need for this study was made apparent during research into the design of an electronic school dictionary, where some learners expressed concern about younger children being exposed to "inappropriate" illustrations in school dictionaries.This article is placed in the South African context and shows how this is a sensitive and relevant topic in South Africa, due to the different cultures that are represented.The article shows how South African school dictionaries currently treat these words, and investigates whether they should be treated any differently. The study includes interviews with primary school teachers and parents, and contains descriptions of existing school dictionary entries, both electronic and print.Literature on the following aspects is covered: taboo topics in dictionaries, cultural aspects of sex education in South Africa, and sex education in primary schools globally.The article will show why it is important to treat these terms in a school dictionary in a clear and unambiguous way, despite this causing potential discomfort to some users. The article will conclude with recommendations for the treatment of human reproductive organs in primary schools, as well as recommendations for further research in this area.Keywords: culture, human reproductive organs, pedagogical lexicography, primary school dictionary, school dictionary, sex organs, sexuality education, taboo